2017
DOI: 10.1111/1758-5899.12523
|View full text |Cite
|
Sign up to set email alerts
|

Partial Two‐Way Mirror: International Organization Budget Transparency

Abstract: This paper evaluates the budget transparency of international organizations. Building on IMF, OECD, IPSAS, and Open Budget Survey standards for sovereign‐state budget transparency, we create a 93‐item budget transparency measure reflective of international organization characteristics. International organizations are important global dispensers of accumulated knowledge. This includes the purveying of advice on member state budget transparency. Despite this role, we find only partial budget transparency among o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The legitimacy crisis stemming from the confluence of events (long-standing issues over accountability; oil-for-food and UNSAS' loss of legitimacy; close voting on alternative standards; the emergence of IPSAS) presented reformers with an opportunity to effect change, regardless of whether the proposed change would actually resolve the intrinsic problems they wanted to redress. In reality the core issues lay with those vested with decision-making powers, and improved financial reporting does not necessarily lead to improved decision-making transparency, as evidenced by Moloney and Stoycheva's (2018) study on budgetary disclosures in IOs. Politicians and senior government decision makers need to resist calls for a quick response to a crisis of legitimation to ensure that the problem(s) is correctly identified before a solution(s) in the form of a major accounting change is applied as a remedy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The legitimacy crisis stemming from the confluence of events (long-standing issues over accountability; oil-for-food and UNSAS' loss of legitimacy; close voting on alternative standards; the emergence of IPSAS) presented reformers with an opportunity to effect change, regardless of whether the proposed change would actually resolve the intrinsic problems they wanted to redress. In reality the core issues lay with those vested with decision-making powers, and improved financial reporting does not necessarily lead to improved decision-making transparency, as evidenced by Moloney and Stoycheva's (2018) study on budgetary disclosures in IOs. Politicians and senior government decision makers need to resist calls for a quick response to a crisis of legitimation to ensure that the problem(s) is correctly identified before a solution(s) in the form of a major accounting change is applied as a remedy.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of accounting reforms having resolved these organisational issues stemming from a lack of accountability is at best mixed. Bergmann and Fuchs (2017) as well as Moloney and Stoycheva (2018) found evidence that adopting international standards for IOs can bring some improvements in transparency. Both papers also found that standards adoption could prompt meaningful debates over existing financial reporting complexities.…”
Section: Rationalities For Accounting Reformsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study focuses on the introduction of transparency measures (especially access‐to‐information policies) within IPAs (), whereas the second one addresses the establishment of bureaucratic oversight mechanisms over time (). In another comparative study, Alesani et al () focus on a narrow reading of the accountability concept as financial and non‐financial disclosure of information in annual reports (for another recent study on budget transparency see Moloney and Stoycheva ). Similar to Geri (), the authors use a checklist approach that divides the concept into eight sections.…”
Section: State Of the Art: Studying Management Change In Ipasmentioning
confidence: 99%
“…Yet if such structures do not exist, are weak, disembodied, or false at the global level, what are the implications for an IO administration agenda? This includes acknowledging any implications for IO administrative research in typical public administration studies as such as leadership (Xu & Weller, 2019), personnel management, collaborative governance, and budgeting (Moloney, 2019; Moloney & Stoycheva, 2018; Patz & Goetz, 2019), to name a few.…”
Section: Opportunities For Public Administration Analysesmentioning
confidence: 99%